Variation and optionality in clitic climbing in Argentinean Spanish - Ioanna Sitaridou (Universitat Autònoma de Barcelona, 2015)
Since Cinque’s (2006:31-32) four-way typology of languages in terms of clitic climbing (CC, herein), those in which CC displays optionality, such as Argentinean Spanish (ArgSp, herein), remain poorly understood. This paper aims to address this need. Here, we show that: (i) empirically, CC has remained a prevalent option in spoken ArgSp since its incipient stage (Davies 1995), yet at the same time we reveal significant diatopic variation in terms of optionality; (ii) theoretically, we capture this optionality partly in terms of ‘parametric hierarchies’ (Biberauer & Roberts 2012) with no considerable impact otherwise on any macro/meso-parameter in this variety. However, in order to fully explain our data, we postulate that the macro-parameter setting makes a Pool of Variants (in the spirit of Adger (2013) and Adger & Smith (2007)) available, in which there are options for CC spell out: proclisis on the matrix or enclisis on the embedded verb(s). Crucially these options do not yield interpretive effects and, therefore, the drive behind the clitic position is lexical. The probability with which one of the clitic spell out positions is selected is claimed to depend at least in part on frequency, behind which we expect a variety of sociolinguistic factors.